Analysis of Plate Raw Material Control with Continuous Review System Method - Ganendra, Devara Priya; Aryanny, Enny (Journal La Multiapp, 2025)
In today's era of globalization, many new companies have emerged, both companies engaged in services, manufacturing, and trade. One of the largest assets in the company PT. XYZ is raw material inventory. Raw material inventory is goods that are stored and used for the production process that are adjusted to the usage schedule. Therefore, in order to avoid high raw material inventory costs, the company must have a proper raw material inventory system by using the proposed method as a comparison, namely the continuous review system method. Plate inventory control was obtained in August 2023 - July 2024 with a total inventory cost using the company method of IDR 292,324,000 and the Continuous Review (s, Q) System method of IDR 144,722,000 with cost savings of IDR 147,602,000 and a cost reduction percentage of 50.4%. After forecasting the plate requirements for August 2023 - July 2024, plate inventory control was obtained with an order quantity of 6,560 sheets and a reorder point of 846 sheets with a total inventory cost of IDR 220,902,000.